Exploring influences on food choice in a large population sample: The Italian Taste project. (July 2017) - Monteleone, E.; Spinelli, S.; Dinnella, C.; Endrizzi, I.; Laureati, M.; Pagliarini, E.; Sinesio, F.; Gasperi, F.; Torri, L.; Aprea, E.; Bailetti, L.I.; Bendini, A.; et al.
Highlights: I talianT aste is a large-scale study aimed at exploring influences on food choice. IT explores the complex interplay of factors contributing to food preferences. Genetic, physiological, personality, sociocultural factors are considered. Associations among personality, attitudes, PROP, familiarity and liking are shown. Abstract: Food choice is influenced by many interacting factors in humans. Its multidimensional and complex nature is well recognized, particularly within the sensory and consumer food science field. However, the vast majority of the studies aimed at understanding determinants of food choices, preferences, and eating behaviours are affected by important limitations: the limited number of factors that are considered at once and the sample size. Furthermore, sensory and hedonic responses to actual food stimuli are often not included in such studies. The Italian Taste project is a large-scale study (three thousand respondents in three years) launched by the Italian Sensory Science Society aimed at addressing these limitations by exploring the associations among a variety of measures – biological, genetic, physiological, psychological and personality-related, socio-cultural – describing the dimensions of food liking, preference, behaviour and choice, and their relevance in determining individual differences within a given food culture framework. In addition, the study includes also the collection of sensory and hedonic responses to actual food stimuli commonly consumed in Italy and prepared to elicit a variation in the strength (from weak to strong) of bitterness, sweetness, saltiness, sourness, pungency, umami and astringency. The aims of the present paper are twofold. Firstly, the paper is aimed to illustrate the variables selected to explore the different dimensions of food choice and to report the experimental procedure adopted for data collection. Secondly, the paper is aimed at showing the potential of the Italian Taste dataset on the basis of the data collected in the first year of the project. For the purpose, we selected a small number of variables known to influence food choices from data collected in the first year of the project on 1225 individuals.